The temporal elements of emotional identification with film characters - McCormick, Stephanie, author; Romagni, Domenica, advisor; MacKenzie, Matt, committee member; Snodgrass, Jeffrey, committee member (Colorado State University. Libraries, 2020)
I argue that the subjective experience of time passing, felt duration, is a crucial element in the emotional and immersive experience of narrative films. First, I review multiple theories of emotional identification to conclude that the most accurate and thorough account is provided by the simulation theory of emotions. Growing from this account, I establish a framework of emotional engagement (general and emotional identification) and immersion (emotional and temporal). Film theories about emotional engagement often overlook felt duration despite it being a feature of emotional experiences. A film's depiction of a character's felt duration facilitates the audience's emotional engagement and immersion. Additionally, the audience's felt duration can be manipulated by the film's pacing techniques to further engagement and immersion. There are two main upshots of my thesis I will briefly outline in the last chapter: aesthetic value and ethical value. The emotional and temporal experiences of the audience are vital to the understanding of narratives and the experience of films. Emotional identification exercises our capacity to relate to other people. This affects our ability to empathize and treat other people. In this thesis, I draw attention to felt duration as an element of emotional engagement and immersion that often goes unacknowledged.
Keywords: engagement; immersion; subjective experiences; felt duration; emotional identification; narrative film